Patient expectations and the paradigm shift of care in emergency medicine - Lateef, Fatimah (Medknow Publications, 2011)
Patient expectation in health care continues to increase and this is something that needs to be managed adequately in order to improve outcomes and decrease liability. Understanding patients’ expectations can enhance their satisfaction level. In the environment of the Emergency Department, with the acutely ill, serious and time-dependent issues as well as high level of stress, managing patient expectations can indeed be challenging. This paper discusses patients expectations and proposes implementation of elements of patient-centered care and value-based care into our existing health care systems today.